Design of Rice Husks Gasification Stove - Aulia Eka Wulandari; Sekar Madu Kusumawardani; Mutiara Amelia Sabrina; Sofi Arofah; Siti Nur Shifa Sholihat; Dadi Rusdiana; Tri Suwandi; Muhammad Aziz (Universitas Pendidikan Indonesia (UPI), 2021)
The human population increases every year, reported from the official website of the United Nation, in 2011 the world population reached 7 billion people. Then in 2016 reached 7.4 billion people and the world population in 2020 reached 7.7 billion people. It is estimated that by 2030 it will grow to 8.5 billion people and by 2050 to reach 9.7 billion inhabitants. which makes energy needs also increase. With these facts, we design gasification stove biomass energy that aims to reduce the use of non-renewable fuels. The study aims to design a rice husks gasification stove to minimize agricultural waste. In this study, there is an innovation in tar reduction using dolomite as a catalyst. This research uses qualitative research methods that are presented descriptively. The gasification stove design is inspired by the oil stove with the addition of an iron pipe that serves as an oxygen supplier. The design of gasification stoves using rice husk as fuel was successfully carried out. This stove is proven to be one of the tools to maximize the potential of using rice husks as fuel. Finally, we hope that this research can continue to be refined in further studies to maximize the utilization of rice husk waste as renewable alternative energy.